FATTY ACID PROFILE OF UPLAND COTTON GENOTYPES THROUGH NIR-NEAR-INFRARED SPECTROSCOPY - S. F. Kazmi; N. U. Khan; S. Gul; I. Ali (Journal of Animal and Plant Sciences, 2015)
The research work comprising genetic studies for oil, fatty acid profile, seed cotton yield and lint percentage in eight parental lines (SLH-284, CIM-446, CIM-473, CIM-496, CIM-499, CIM-506, CIM-554, CIM-707) and their F3 populations was carried out during 2011 and 2012 at The University of Agriculture, Peshawar and Nuclear Institute for Food and Agriculture, Peshawar - Pakistan. The genetic potential of genotypes in terms of genotypic (GCV) and phenotypic coefficient of variance (PCV), heritability (broad sense), and genetic gain were determined for all the traits. Mean squares revealed significant (p≤0.01) variations among parental cultivars and F3 population for all the traits, indicating greater genetic variability in the breeding material. Overall, the F3 populations revealed greater mean values than parental genotypes for oil content, linoleic acid, stearic acid and ratio of unsaturated/saturated fatty acids while for other traits the average mean values were comparable. Genotypic variances were found greater than environmental variances for all traits. The GCV and PCV for all the traits ranged from 1.62 to 37.41 and 1.87 to 39.21, respectively. Broad sense heritability was high for all the traits ranging from 0.75 (lint percentage) to 0.99 (saturated fatty acids) with maximum genetic gain for seed cotton yield (19.73 g). Seed cotton yield revealed positive correlation with all traits, however, it was highly significant with stearic acid and saturated fatty acids, significant (p≤0.05) with oil content, linoleic acid, unsaturated fatty acids and lint percentage indicating that increase in fatty acids had positive impact on seed cotton yield. The parental lines CIM-707, CIM-554, SLH-284 and CIM-496 performed well for all traits. The F3 populations CIM-707 × CIM-554 and CIM-707 × CIM-499 revealed best performance for oil content and fatty acids profile. The F3 populations CIM-446 × SLH-284 and CIM-496 × CIM-499 excelled other F3 populations and parental cultivars for seed cotton yield and lint percentage with desirable oil quality traits. These promising F3 populations can be used in future breeding for enhancement in fatty acid profile and yield traits.
Keywords: Cottonseed oil; fatty acid profile; lint percentage; seed cotton yield; genetic variability; correlation; upland cotton